Electromagnetic coupling between a GTEM-cell and a device under test: a hybrid modal-analysis & method-of-moments approach - Zellerhoff, M.; Hannemann, J.; Klinkenbusch, L. (IEEE Antennas and Propagation Society International Symposium 2002, 2002)
Based on the increasing importance of EMC-problems there is a great interest in measurement devices like GTEM-cells (Giga(Hz)-TEM cells). They promise to allow compact and low-cost emission as well as susceptibility tests up to very high frequencies. Expensive measurement procedures in open-area test sites or within semi-anechoic chambers would become obsolete in many cases. To estimate the quality and reliability of GTEM-cell measurements it is necessary to have detailed knowledge about the processes within the cell and, in particular, about the interactions between the cell and the DUT (device under test). Due to the high frequency and the cell's dimensions (ca. 5 m in length) a purely numerical simulation while using standard techniques such as finite elements, method of moments (MoM) or FDTD is expensive and, moreover, inefficient and unnecessary since the GTEM-cell is a mostly empty homogeneous TEM-waveguide. Analytical models allow only the investigation of empty cells or cells loaded with canonical objects. As outlined in the paper, a suitable way to reduce the numerical complexity of the general problem is the use of a hybrid method, such as the combination of a modal analysis with the MoM.